2021
DOI: 10.1177/15330338211036533
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nomogram for Predicting Cancer-Specific Survival in Patients With Spinal Chordoma: A Population-Based Analysis

Abstract: Background: Chordoma is a rare malignant bone tumor, and the survival prediction for patients with chordoma is difficult. The objective of this study was to construct and validate a nomogram for predicting cancer-specific survival (CSS) in patients with spinal chordoma. Methods: A total of 316 patients with spinal chordoma were identified from the SEER database between 1998 and 2015. The independent prognostic factors for patients with spinal chordoma were determined by univariate and multivariate Cox analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…The National Comprehensive Cancer Network for Bone Cancer screening guidelines also clearly state the significant role of neoadjuvant and adjuvant multidrug chemotherapy in improving the prognosis of patients with osteosarcoma and Ewing’s sarcoma ( 16 ). This conclusion is somewhat similar to the study we did previously ( 7 ). However, radiation therapy and chemotherapy were not included as statistically significant variables in our study in the nomogram.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The National Comprehensive Cancer Network for Bone Cancer screening guidelines also clearly state the significant role of neoadjuvant and adjuvant multidrug chemotherapy in improving the prognosis of patients with osteosarcoma and Ewing’s sarcoma ( 16 ). This conclusion is somewhat similar to the study we did previously ( 7 ). However, radiation therapy and chemotherapy were not included as statistically significant variables in our study in the nomogram.…”
Section: Discussionsupporting
confidence: 93%
“…A nomogram, a simple visualization of Cox regression results, can help clinicians predict the prognosis with significant advantages and greatly improve predictive accuracy (7). In a previous study, Zhou et al constructed a prognostic nomogram model for patients with all types of primary spinal tumors (8).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to age, logistic regression analysis showed that tumor grade, tumor stage, and histological type of tumor are also key factors. Te prognosis of survival in patients with primary tumors of the spine has been welldocumented to correlate with these factors, and many authors have constructed related nomograms [10,[18][19][20][21][22][23][24][25][26]. In our previous studies, we have shown that tumor grade, tumor stage, and histological type of tumor are the key factors infuencing postoperative OS in patients with primary spinal tumors, which is consistent with the results of this study [25].…”
Section: Discussionsupporting
confidence: 90%
“…Nomograms, the prognostic device capable of combing multiple parameters that can reveal the relationship between chordoma and prognosis with greater accuracy and convenience than every single parameter that reflects only limited associations with a particular aspect of chordoma, and thus are now widely used for individualized prediction of tumor patients [17,18]. In the past, nomograms based on traditional Cox proportional hazard regression models and Kaplan-Meier methods have been employed extensively to predict survival outcomes in chordoma patients [16,[19][20][21]. However, it is a non-negligible drawback that competing risk (in other word, non-cause-specific death), such as non-cancer-specific death (NCSD), is treated as censored data in the traditional Cox and Kaplan-Meier survival analyses [22].…”
Section: Introductionmentioning
confidence: 99%